2016
DOI: 10.1021/acs.jpclett.6b02624
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanical Calculations of Vibrational Sum-Frequency-Generation (SFG) Spectra of Cellulose: Dependence of the CH and OH Peak Intensity on the Polarity of Cellulose Chains within the SFG Coherence Domain

Abstract: Vibrational sum-frequency-generation (SFG) spectroscopy is capable of selectively detecting crystalline biopolymers interspersed in amorphous polymer matrices. However, the spectral interpretation is difficult due to the lack of knowledge on how spatial arrangements of crystalline segments influence SFG spectra features. Here we report time-dependent density functional theory (TD-DFT) calculations of cellulose crystallites in intimate contact with two different polarities: parallel versus antiparallel. TD-DFT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(98 citation statements)
references
References 26 publications
2
96
0
Order By: Relevance
“…Because molecular selfassembly fully covers gold substrates, the difference in VSFG intensity reflects various domain conformations, but not surface coverage: e.g., domains with strong VSFG signals consist of head-to-tail conformations, because they are non-centrosymmetric, whereas domains with weak signals are composed of head-to-head configurations. 51 However, there is much more information to be learned than what the VSFG intensity image can reveal, because in the HD VSFG image, each pixel encodes a phase-resolved HD VSFG spectrum. To take advantage of the rich spectral information, we further characterize each domain by comparing all the spectral patterns of their imaginary spectra (corresponding to absorptive spectra), 30,33,34,36,47 including peak position, phase and line shapes.…”
Section: Figurementioning
confidence: 99%
“…Because molecular selfassembly fully covers gold substrates, the difference in VSFG intensity reflects various domain conformations, but not surface coverage: e.g., domains with strong VSFG signals consist of head-to-tail conformations, because they are non-centrosymmetric, whereas domains with weak signals are composed of head-to-head configurations. 51 However, there is much more information to be learned than what the VSFG intensity image can reveal, because in the HD VSFG image, each pixel encodes a phase-resolved HD VSFG spectrum. To take advantage of the rich spectral information, we further characterize each domain by comparing all the spectral patterns of their imaginary spectra (corresponding to absorptive spectra), 30,33,34,36,47 including peak position, phase and line shapes.…”
Section: Figurementioning
confidence: 99%
“…The transition dipole moments of the SFG-active OH stretch modes are in the (200) plane of the cellulose I unit cell with specific tilt angles from the chain axis. 30,[39][40] In contrast, the transition dipole moments of the SFG-active CH and CH 2 stretch modes are off the (200) plane. Thus, the OH dipoles can be enhanced when two crystallites are unidirectional (parallel) and cancelled when one crystallite is rotated by 180 o along the a-axis of the unit cell, making two crystallites bidirectional (antiparallel) to each other.…”
Section: Introductionmentioning
confidence: 99%
“…156,157 So far, these novel techniques have not been widely applied to polymer interface studies. Additionally, molecular dynamics simulations, ab initio calculations, and time-dependent density functional theory can assist to predict and interpret the vibrational signatures obtained from SFG-VS. [158][159][160] Future work utilizing these advanced methodologies to interpret polymer interfaces would improve the understanding of molecular behaviors at buried polymer interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…We need to mention that many biomolecules can be considered as natural polymers, such as cellulose, collagen polypeptide, deoxyribonucleic acid (DNA), and polymerized amyloid b-peptide. The abovementioned biopolymers have been extensively examined by SFG-VS, 160,[177][178][179][180][181] but were not discussed in this review. Excellent review articles related to the biological subjects of the SFG-VS can be found elsewhere.…”
Section: Discussionmentioning
confidence: 99%